Decoupling the effects of nutrition, age, and behavioral caste on honey bee physiology, immunity, and colony health - Corona, Miguel; Branchiccela, Belen; Alburaki, Mohamed; Palmer-Young, Evan C.; Madella, Shayne; Chen, Yanping; Evans, Jay D. (Frontiers in Physiology, 2023)
Nutritional stress, especially a dearth of pollen, has been linked to honey bee colony losses. Colony-level experiments are critical for understanding the mechanisms by which nutritional stress affects individual honey bee physiology and pushes honey bee colonies to collapse. In this study, we investigated the impact of pollen restriction on key markers of honey bee physiology, main elements of the immune system, and predominant honey bee viruses. To achieve this objective, we uncoupled the effects of behavior, age, and nutritional conditions in colonies of similar size, demography, and genetic background. Our results showed that the expression of storage proteins, including vitellogenin (vg) and royal jelly major protein 1 (mrjp1), were significantly associated with nursing, pollen ingestion, and older age. On the other hand, genes involved in hormonal regulation (mfe, ilp1, ilp2), exhibited higher expression levels in young foragers from colonies not experiencing pollen restriction. In contrast, pollen restriction induced higher levels of insulin-like peptides in old nurses. On the other hand, we found a strong effect of behavior on the expression of all immune genes, with higher expression levels in foragers. In contrast, the effects of nutrition and age were significant only the expression of the regulatory gene dorsal. We also found multiple interactions of the experimental variables on viral titers, including higher DWV titers associated with foraging and an age-related decline. In addition, nutrition significantly affected DWV titers in young nurses, with higher titers induced by pollen restriction. Finally, correlation, PCA, and NMDS analyses proved that behavior had had the strongest effect on gene expression and viral titers, followed by age and nutrition. These analyses also support multiple interactions among genes and virus analyzed, including negative correlations between the expression of genes encoding storage proteins associated with pollen ingestion and nursing (vg and mrjp1) with the expression of immune genes and DWV titers. Our results provide new insights into the proximal mechanisms by which nutritional stress is associated with changes in honey bee physiology, immunity, and viral titers.